Wage Incentive Profiles in Dual Labor Markets - Marco Di Cintio; Emanuele Grassi (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper formalizes the use of flexible labor contracts in an efficiency wage framework and derives market dualism as an endogenous outcome. By allowing temporary contracts to be either renewed or converted into permanent contracts, new theoretical insights emerge both on the equilibrium wage structure and the incentive problem faced by workers and firms. Since temporary workers weigh the outside option of entering the labor market through permanent positions, the rate at which fixed-term contracts are converted into open-ended contracts is itself an incentive device which acts as a substitute for the wage. It follows that, even if temporary workers face a higher job loss risk, firms pay a wage differential in favor of permanent workers. The model also predicts that in equilibrium firms hire exclusively under flexible contracts, then half of them is converted into stable contracts while the remaining contracts are left to expire. Thus, in steady state, firms let permanent positions to survive in order to sustain the wage incentive structure.
Keywords: J31; J41; J63; 330; Dual Labor Market; Efficiency Wages; Wage Differentials; Flexible Contracts